2004
DOI: 10.1038/modpathol.3800089
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral carcinomas of the breast with local recurrence: analysis of genetic relationship of the tumors

Abstract: Local recurrence of bilateral breast carcinomas is rare, but of biological interest, since it is unclear as to which tumor the local recurrence is related to, the ipsilateral or the contralateral, or whether it is an independent neoplasm. The aim of this study was to investigate the genetic relationship of bilateral breast carcinomas to each other and to their local recurrences. Eight cases of bilateral breast carcinomas, five with and three without local recurrence were analyzed using a microsatellite assay f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] In this updated analysis, the technique was applied to 57 cases of invasive carcinoma treated with BCT in which an IBTR occurred. Of these 57 cases, 34 (60%) had the same or an almost identical pattern of genetic mutations as the corresponding initial carcinoma, indicating they were genetically related, persistent neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16] In this updated analysis, the technique was applied to 57 cases of invasive carcinoma treated with BCT in which an IBTR occurred. Of these 57 cases, 34 (60%) had the same or an almost identical pattern of genetic mutations as the corresponding initial carcinoma, indicating they were genetically related, persistent neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the PCR-based LOH mutation patterns can reliably establish the clonality of one carcinoma relative to another. [7][8][9][10][11][12][13][14][15][16] An LOH mutation pattern comparison using primers targeted to frequently deleted tumor suppressor genes is an ideal method for accurately distinguishing if an IBTR after definitive therapy represents a new primary versus a recurrence of the index lesion. This IBTR data could potentially define the efficacy of local radiation therapy modalities (whole breast vs. partial breast irradiation).…”
mentioning
confidence: 99%
“…In general, these studies have shown that clonality is quite common for mucosal cancers of the head and neck (23) and bladder (24). However, for sites with paired organs, such as breast (25)(26)(27)(28) and lung (29)(30)(31), the vast majority of new contralateral primaries seem to be biologically independent. The issue does not seem to have been studied in melanoma, but the wide anatomic distribution of melanomas and the absence of a plausible mechanism for the seeding of clonal cells in distant parts of the skin argue against the frequent clonality of multiple primaries in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…A contrasting picture emerges from studies of contralateral cancer of the breast and lung. Authors of these studies have generally reached the conclusion that the tumors are typically independent for contralateral breast cancers (Kollias et al, 2000; Janschek et al, 2001; Stenmark-Askmalm et al, 2001; Imyanitov et al, 2002; Tse et al, 2003; Chunder et al, 2004; Regitnig et al, 2004; Schlechter et al, 2004), although corresponding studies of new ipsilateral breast cancers indicate that these are predominately of clonal origin (Goldstein et al, 2005a; 2005b). Studies in lung cancer have been conducted using microsatellite markers to distinguish microsatellite instability (MSI) (Leong et al, 1998; Huang et al, 2001; Shin et al, 2001; Dacic et al, 2005; Geurts et al, 2005) and several have tested mutations in TP53 and/or K-ras (Sozzi et al, 1995; Lau et al, 1997; Hiroshima et al, 1998; Holst et al, 1998; Matsuzoe et al, 1999; Shimizu et al, 2000; Shin et al, 2001; van Rens et al, 2002; Murase et al, 2003).…”
Section: Introductionmentioning
confidence: 99%